CHARACTERISTICS OF OBSCURE UTTERANCES IN THE LECTURER-STUDENT COMMUNICATION - KABWE KANTANDA, MUPEMBA (IJRDO- Journal of Educational Research, 2022)
This article investigates into characteristics of obscure utterances occurring during lectures. The problem is communication impendence during lectures due to obscure utterances.  The research question is “what are the characteristics of obscure utterances that occur in the lecturer-Student Communication?” Inappropriateness and misusage of words are the hypothesis of this article. To verify this hypothesis, classroom observations were used in order to collect both lecturer’s and students’ utterances and examine them on the basis of lexical, compositional, and utterance analyses. So, this article aims at finding out the characteristics of obscure expressions during lectures so as to suggest strategies to avoid them. The results revealed 6 characteristics: no relationship between the utterance and the intention, no relationship between the question and the answer, using words and phrases that do not exist actually, delivering false knowledge, lack of clarity in the use of key word, and poor explanation.